Using the second generation Web 2.0 tools in developing university EFL students’ english language skills - Asmaa Naim Abusamra; Teguh Triwiyanto (Jurnal Inovasi Teknologi Pendidikan, 2023)
In 2020, conducting education at a distance was obligatory while the world fought the coronavirus disruption. Technology utilization in distance education has demonstrated its significance in teaching English to instructors and learners. This quantitative study examines university EFL learnersâ€™ perceptions regarding using second-generation Web 2.0 tools (Quizizz, Socrative, Edmodo, and Quizlet) to develop their English skills. This study was conducted with 150 students of the general English language requirement course at the University College of Applied Sciences in Gaza. The results of this study indicate that the participants appeared to have positive attitudes towards using Web 2.0 tools in general. The study results further indicate that both intermediate and low-level students reported more positive opinions about implementing the digital tools individually or all together when compared to other advanced-level students. The participants differed significantly in their perceptions of the awareness and actual usage of the Web 2.0 tools. The implications of this study indicate that these repeatedly used Web 2.0 tools as curricular tasks could be substituted or replaced with other digital tools to alleviate the oversaturation and reluctance to use digital tools by EFL learners.Â